# Find x:Find x: (3x+7)(x-1) = 24.

*print*Print*list*Cite

### 3 Answers

The equation to be solved is : (3x+7)(x-1) = 24

(3x+7)(x-1) = 24

=> 3x^2 + 4x - 7 = 24

=> 3x^2 + 4x - 31 = 0

x1 = -4/6 + sqrt (16 + 372) /6

=> -2/3 + (sqrt 97)/6

x2 = -2/3 - (sqrt 97)/6

**The roots of the equation are -2/3 + (sqrt 97)/6 and -2/3 - (sqrt 97)/6**

(3x + 7)(x - 1) = 24

3x^2 - 3x +7x - 7 = 24

3x^2 +4x -31 = 0

From this point you can apply the quadratic formula and get two x values. Depending on the situation, one of them might be extraneous.

3x^2 - 3x + 7x - 7 = 24

We'll combine like terms:

3x^2 + 4x - 31 = 0

We'll apply quadratic formula:

x1 = [-4+sqrt(16+372)]/6

x1 = (-2+sqrt97)/3

x2 = (-2-sqrt97)/3